Mesoporous coupled ZnO/TiO2 Photocatalyst Nanocomposites for Hydrogen Generation - Hussein, Abdulmenan M.; Mahoney, Luther; Kibombo, Harrison; Wu, Chia-Ming; Shende, Rajesh (Journal of Renewable and Sustainable Energy, 2013)
The present work investigates mesoporous coupled ZnO-TiO2 based nanocomposites towards photocatalytic hydrogen generation. The effect of Zn2+ loadings was examined on the photocatalytic activities of the sol-gel derived ZnO-TiO2 nanocomposites employing a structure-directing template. ZnO-TiO2 nanocomposites were characterized by powder X-ray diffraction, transmission electron microscopy, UV-vis diffuse reflectance spectroscopy, nitrogen isotherm, Raman, and electrochemical impedance spectroscopy (EIS) methods. The photocatalytic H2 evolution of the ZnO-TiO2 suspensions was evaluated in an aqueous methanol medium under UV illumination. The Zn2+ concentrations utilized to prepare ZnO-TiO2 nanocomposites were found to have significant effect on the specific surface area, pore volume, and photocatalytic activity. The H2 evolution results obtained with ZnO-TiO2 nanocomposites were compared with H2 generation using commercial TiO2 P25 and individual ZnO nanoparticles. The photocatalytic activity of ZnO-TiO2 composite enhanced significantly as compared to P25 or ZnO nanoparticles. With respect to an increment in Zn2+ loading, the photocatalytic activity of the composite increased and reaching an optimal H2 production of 17.3 ml/g of catalyst for the ZnO-TiO2 composite containing 30 wt. % ZnO (30ZnO). The specific surface area of the samples increased from 19 (single ZnO) to 122 m2/g for ZnO-TiO2 composite containing 50 wt. % ZnO (50ZnO). With an appropriate Zn2+ presence in ZnO-TiO2 nanocomposites, the specific surface area, total pore volume, charge transfer, and photocatalytic activity were significantly improved. Particularly, the samples containing 30 and 50 wt. % (30ZnO and 50ZnO) showed higher photocatalytic activity towards hydrogen generation, which attributed to higher specific surface areas, larger pore volumes, and lower interface resistance as confirmed by adsorption-desorption isotherms and EIS measurements, respectively. Hence, ZnO-TiO2 composites with higher than 50 wt. % ZnO were found to be not favorable to attain reasonable photocatalytic activity toward hydrogen generation as specific surface area and pore volume were drastically decreased.
Keywords: Mesoporous; photocatalyst; hydrogen generation